1981
DOI: 10.1152/ajprenal.1981.240.3.f222
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between sodium and bicarbonate transport in the rat proximal convoluted tubule

Abstract: The relationship between net sodium and bicarbonate transport was studied by microperfusion of proximal convoluted tubules and peritubular capillaries. Bicarbonate absorption was unchanged as long as the sodium concentration remained above 40 meq/liter, despite reduction of sodium transport to 10% of its control value. At a sodium concentration of 5 meq/liter, fluid absorption was completely abolished but bicarbonate transport was reduced to 39% of its control value. Even at reduction of luminal and peritubula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

1982
1982
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 0 publications
2
33
0
Order By: Relevance
“…To ascertain whether flow-induced changes in ammonia production depended upon the flow-induced changes in the rate of fluid reabsorption observed in the proximal tubule (17), we perfused proximal segments with perfusate containing 25 mM sodium (sodium chloride isoosmotically replaced by mannitol) and 1.0 mM amiloride hydrochloride, a condition that has been shown to reduce fluid reabsorption in the rat proximal tubule (18). We found that fluid reabsorption by the mouse proximal tubule fell to -0.11±0.36 nl/mm per minute (n = 3) from a control value 1.09±0.26 nl/mm per minute.…”
Section: Resultsmentioning
confidence: 99%
“…To ascertain whether flow-induced changes in ammonia production depended upon the flow-induced changes in the rate of fluid reabsorption observed in the proximal tubule (17), we perfused proximal segments with perfusate containing 25 mM sodium (sodium chloride isoosmotically replaced by mannitol) and 1.0 mM amiloride hydrochloride, a condition that has been shown to reduce fluid reabsorption in the rat proximal tubule (18). We found that fluid reabsorption by the mouse proximal tubule fell to -0.11±0.36 nl/mm per minute (n = 3) from a control value 1.09±0.26 nl/mm per minute.…”
Section: Resultsmentioning
confidence: 99%
“…First, Giebisch et al (33) found that H+ secretion was reduced when NaHCO3 was infused acutely to obtain a plasma HCO-concentration of 44 mM. Second, Chan and Giebisch (34) observed that increasing peritubular HCO-concentration from 2 to 40 mM inhibited HCO-reabsorption. However, the interpretation of these data as indicating an independent effect of peritubular HCO-concentration is complicated by the presence of extracellular volume expansion in the former and by the presence of an extremely low peritubular Pco2, and thus high pH, in the latter.…”
Section: Methodsmentioning
confidence: 99%
“…There are conflicting reports concerning the extent to which luminal fluid may be acidified between the seminiferous tubules and the caput epididymidis (Levine & Kelly, 1978;Caflisch & DuBose, 1990). It is well documented that proximal tubule fluid is acidified by H¤ secretion (see review in Alpern & Rector, 1996;also Lucci et al 1980;DuBose et al 1981) and there is evidence that the Na¤-H¤ antiporter contributes largely to this (Chan & Giebisch, 1981;Howlin et al 1985;Preisig et al 1987). The apical Na¤-H¤ exchanger has also been implicated in epididymal acidification (Au & Wong, 1980).…”
Section: ------------------------------------------------------------mentioning
confidence: 99%